Analisis Efektivitas Siklus Penjualan dan Penagihan Pada PT Unilever Indonesia Tbk: Studi Periode 2022–2024 - Amelia Fernanda; Aulia Anisa; Muh. Salman Fadlurahman; Jusfebrianti Jusfebrianti; Devi Eva Rianti (Universitas 45 Surabaya, 2025)
This study aims to analyze the effectiveness of the sales and collection cycle of PT Unilever Indonesia Tbk during the 2022–2024 period using a descriptive quantitative approach through a case study based on annual financial statements obtained from the Indonesia Stock Exchange. The analysis was conducted by calculating Receivable Turnover (RT) and Days Sales Outstanding (DSO) and examining their trends. The results show that RT increased from 9.77 times in 2022 to 16.64 times in 2024, while DSO decreased from 37.37 days to 21.94 days. These findings indicate improved receivables management effectiveness, enabling the company to convert receivables into cash more quickly and reduce the risk of bad debts. However, the decline in net sales from IDR 41.22 million in 2022 to IDR 35.14 million in 2024 highlights the need for a more aggressive sales strategy. Overall, the effectiveness of the sales and collection cycle at PT Unilever Indonesia Tbk can be considered good, although long-term financial sustainability requires a balance between credit policy, marketing strategy, and digitalization optimization.